Mesenchymal stem/stromal cells as a therapeutic for sepsis: a review on where do we stand? - Courtney Premer; Joshua M. Hare; Sarah Y. Yuan; Jason W. Wilson (Stem Cell Research & Therapy)
Abstract Sepsis is one of the leading causes of morbidity and mortality in the United States and Worldwide despite advances in quick recognition and early antibiotics, fluids, and vasopressors. Mesenchymal stem/stromal cells (MSCs) have gained attention as a biologic therapy given their unique anti-inflammatory, immunomodulatory, and anti-bacterial characteristics. MSCs have had success in treating a range of diseases, however limited clinical trials exist specifically for MSC use in sepsis. This article reviews the properties of MSCs that make them favorable for treating sepsis, as well as the current state of clinical trials. All clinical trials presented here demonstrated MSC safety, with a mixture of efficacy results and a heterogeneity of trial methods. Ultimately, MSCs are a promising novel therapeutic for sepsis, however a consensus in cell source, dosage, preparation, and delivery needs to be further investigated for MSCs to transition from bench to bedside and become a true therapeutic for sepsis. Graphical abstract